Doprowadź wyrażenia do najprostszej postaci i oblicz ich wartość dla podanych zmiennych :
a) (x-3)²+2(2x+1)²-3(x-2)(x+2) dla x= -2
b) -3(2x-5)²-(x-4)(x+4)+6(x+2)² dla x= -1
c) (a-2b)²-3(3a-b)(3a+b)+10(2a+3b)² dla a= -1 i b= 1
d) (2a-3b)(3b+2a)-2(a-3b)²-(2a+b)² dla a= 3 i b= -1

3

Odpowiedzi

2010-02-11T21:02:59+01:00
A) (x-3)²+2(2x+1)²-3(x-2)(x+2) dla x= -2
x²-6x+9 +2 (4x²+4x+1) - 3 (x²+4)
x²-6x+9 + 8x²+8x+2-3x²-12
6x²+2x-1
6* (-2)² + 2 * (-2) - 1 = 6 * 4 -4-1 = 24-5 = 19

b) -3(2x-5)²-(x-4)(x+4)+6(x+2)² dla x= -1
-3 (4x²-20x+25) - (x² -16) +6 (x²+4x+4)
-12x²+60x - 75 - x²+16 +6x²+24x+24
-7x² +74x -35
-7 * (-1)² + 74 * (-1) -35 = -7 *1 -75-35 = -7-75-35 = -117

c) (a-2b)²-3(3a-b)(3a+b)+10(2a+3b)² dla a= -1 i b= 1
a²-4ab + 4b² -3 (9a² -b²) +10 (4a²+12ab+9b²)
a²-4ab+4b²-27a²+3b²+40a²+120ab+90b²
14a²+116ab+97b²
14*(-1)² +116*(-1)*1 + 97*1² = 14*1 -116 +97*1 = 14-116+97 = -5

d) (2a-3b)(3b+2a)-2(a-3b)²-(2a+b)² dla a= 3 i b= -1
4a²-9b² -2(a²-6ab+9b²) - (4a²+4ab+b²)
4a²-9b²-2a²+12ab-18b²-4a²-4ab-b²
-2a²-28b²+8ab
-2* (3)²- 28*(-1)² +8*3* (-1) = -2*9 - 28*1 -24 = -18-28-24 = -70
2 3 2
2010-02-11T21:10:16+01:00
A) (x-3)²+2(2x+1)²-3(x-2)(x+2) dla x= -2
b) -3(2x-5)²-(x-4)(x+4)+6(x+2)² dla x= -1
c) (a-2b)²-3(3a-b)(3a+b)+10(2a+3b)² dla a= -1 i b= 1
d) (a-2b)²-3(3a-b)(3a+b)+10(2a+3b)² dla a= -1 i b= 1

a)(-2-3)²+2(2+(-2)+1)²-3(-2-2)(-2+2)=
=-5²+4-4+2²+6+6<tu powinien byc jakis znak>...

b) -3(2x-5)²-(x-4)(x+4)+6(x+2)²=
=-3(2-1-5)²-(-1-4)+6(-1+2)²=
=-5+3+15²+1+4-6+12

2010-02-11T21:12:16+01:00
A) (-2-3)2 + 2(2* -2 + 1)2 - 3(-2-2)(-2 + 2)
(-5)2 + 2(-4 + 1)2 - 3(-4)(0)
25 + 2(-3)2 - 3 * 0
25 + 2*9 - 0
25 + 18 - 0
43

b) -3(2x-5)²-(x-4)(x+4)+6(x+2)²
-3 (4x2 - 25) - x2 + 4x - 4x - 16 + 6(x2 + 4)
- 12x2 + 75 - x2 - 16 + 6x2 + 24
-7x2 + 99

-7 * (-1)2 + 99
-7 * 1 + 99
-7 + 99= 92

c) (a-2b)²-3(3a-b)(3a+b)+10(2a+3b)²
a2 - 4b2 - (9a-3b)(3a+ b) + 10(4a2 + 9b2)
a2 - 4b2 - 27a2 - 9ab - 9ab - 3b2 + 40a2 + 10b2
14a2 - 18ab + 6b2
14 * (-1)2 - 18*-1*1 + 6* (1)2
14 * 1 + 18 + 6
14 + 18 + 6
38

d)(2a-3b)(3b+2a)-2(a-3b)²-(2a+b)²
6ab + 4a2 - 9b2 + 6ab - 2(a2 - 9b2) - 4a2 + b2
6ab + 4a2 - 9b2 + 6ab - 2a2 + 18b2 - 4a2 + b2
12 ab - 2a2 + 10b2
12*3*-1 + 2 * (3)2 + 10 (-1)2
-36 + 2*9 + 10*1
-36 + 18 + 10
-36 + 28
-8